Probable Causes And Strategies to Address The Issue of High Rate of Debauchery Among The Youth: With Reference to Erik Erikson’s Fifth Stage of Psychosocial Theory of Personality Development - Emmanuel Tettey; Alex Sarfo-Mensah; Esther Jessica Agyekumwaa Osei (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2023)
Erik Erikson's theory of psychosocial development posits that individuals advance through eight different stages of life, each marked by a crisis that must be resolved in order to successfully move on to the next stage. According to Erikson's theory, successfully resolving these crises leads to the development of a healthy psychosocial identity, while a failure to resolve these crises can result in a less healthy identity or even identity confusion. The youth of today shows a lot of misconduct in the society and this is attributed to the fact that they fail to resolve the conflict at the fifth stage (identity vs role confusion) of psychosocial theory of personality development. The study reveals some of the probable causes of debauchery among others as mass media, bad peer influence, dysfunctional homes, poor parenting styles and lack of education. The study however suggested some strategies to address the issue of high rate of debauchery; education, building strong relationship with the youth, building confidence and self-compassion and good peer influence. It was therefore concluded that teenagers at this time investigate numerous facets of identity and either acquire a coherent sense of who they are or stay confused about who they are and what they want out of life. Parents, on the other hand, are supposed to provide a good parenting style that will not damage the child in terms of identifying himself or herself. It was recommended among others that school authorities and lecturers in higher institutions should intensify efforts in educating the youth on moral values that will enable them acquire a set of beliefs and values on what is right and wrong which will make them excel. Again, institutions can establish policies and procedures for addressing misconduct, including reporting and investigation protocols, as well as consequences for violating standards of behavior.